The Germanic Dental Preterite - A Morphological and Semantic Examination - Phoenix, Elizabeth (2023)
The weak dental preterite is one of the defining features of the Germanic verbal system and is an innovation of the Germanic branch of Proto-Indo-European. This paper aims to examine the likelihood of a Proto-Indo-European construction as the origin of the dental preterite and if any of the relationship between morphology and semantics found in Proto-Indo-European was inherited into the old Germanic languages. This paper follows the periphrastic construction theory and while the reason the imperfective *dhe was utilised remains unclear, this paper will show that as the Germanic languages developed they reached a point where the relationship between form and function became opaque. The weak dental preterite’s function was broadened to be used as a safeguard against further verb system change resulting in the Proto-Indo-European deverbal and denominative verbs no longer being the only weak verbs.